Plan de negocios para la creación de una empresa dedicada a la elaboración y comercialización de sal comestible para personas hipertensas en la ciudad de Quito - Cabrera Morocho, Juan Carlos (2016)
In Ecuador hypertension levels are high, these levels have been increasing in a rapid way the last decade. This is mainly due to feeding habits Ecuadorian society holds; for instance, most Ecuadorians consider salt as an indispensable product when preparing their food. As a result of this excessive consumption of salt people develop diseases that have no cure as it is hypertension. Worrying about health has become a social trend that is increasing especially in important cities as Quito, Guayaquil, and Cuenca. It should be noted that the number of hypertension registered patients found in Quito is dramatic (356.964 hypertensives). This problem has been identified as a business opportunity in Quito where edible salt, for people who suffer from this catastrophic disease and for those who wish to avoid this, could be produced. Nowadays, such a product is not offered in the domestic market, this consideration is essential for the development of this project. For the above reasons mentioned the product will be sustainable over time, will require appropriate strategies to develop the product and the market with an affordable price for people. Finally, in the proposed project it can be seen that the initial investment required is USD 109.815,99, also it has a Leveraged VPN (Net Present Value) of USD 133.229,97 with an internal rate of return (IRR) of 65%, so which it has been forecasted a recovery period of 3 years and 7 months.